Evolution and status of Oecophylla smaragdina as a pest control agent in citrus in the Mekong Delta, Vietnam - Van-Mel, P.; Cuc, N.T.T. (Informa UK Limited, 2000)
Citrus farmers in the Mekong Delta have a long tradition of managing the weaver ant Oecophylla smaragdina (Fabricius). From 1994 to 1998, insecticide use increased significantly (P< 0.01) from 66% to 84% in orchards where O. smaragdina occurred. In 1998, ca 75% of the sweet orange (Citrus sinensis) and 25% of the Tieu mandarin (C. reticulata) orchards had large O. smaragdina populations, due to lower pesticide pressure in the first crop. In orchards with O. smaragdina, farmers sprayed less frequently and used fewer highly hazardous insecticides. Major insecticides used in sweet orange were monocrotophos and alpha-cypermethrin, and those used in Tieu mandarin were methidathion, imidacloprid and fenpropathrin. Expenditure on pesticides was reduced by half when O. smaragdina was abundant, without affecting either the yield or the farmers' income. Therefore, O. smaragdina husbandry is a good example of a traditional practice which should be further promoted as an important component of sustainable citrus production. The experience of those farmers who use no or few pesticides should be drawn upon in developing farmer training programmes or mass media tools to promote IPM in citrus. Farmers practicing ant husbandry were significantly older than those not doing so.